Climbing the Slippery Slope: Investigating Real Estate Developer Strategy - Roche, Julian (Curtin University, 2025)
Real estate developers are key to the future of cities. Yet what they view as strategic and how they craft strategy is not well understood. This research concludes that geographical focus, sectoral priorities, timeframes, land banking and sell vs hold are strategic. Land prices vs construction costs, WFH/online retail, technology and branding, but also comparative planning systems macro-economic and ESG factors and the demands of funders are all important drivers of developer strategy.